CD14+ monocyte‐derived galectin‐9 induces natural killer cell cytotoxicity in chronic hepatitis C. Issue 1 (5th November 2016) - Nishio, Akira; Tatsumi, Tomohide; Nawa, Takatoshi; Suda, Takahiro; Yoshioka, Teppei; Onishi, Yoshiki; Aono, Satoshi; Shigekawa, Minoru; Hikita, Hayato; Sakamori, Ryotaro; Okuzaki, Daisuke; Fukuhara, Takasuke; et al.
Abstract : Natural killer (NK) cell activation is associated with both liver injury and persistent infection in chronic hepatitis C (CHC); however, the detailed mechanism of this activation has not yet been fully elucidated. Because galectin‐9 (Gal‐9) has been reported to be increased in the serum and liver tissue of CHC patients, we investigated the function of Gal‐9 in NK cell activation in CHC. First, we evaluated the function of Gal‐9 on NK cytotoxicity in vitro. Gal‐9 treatment resulted in increased cytotoxicity of naïve NK cells, and the Gal‐9‐activated NK cells demonstrated cytotoxicity toward hepatoma cells and T cells. Additionally, coculturing peripheral blood mononuclear cells (PBMCs) with JFH‐1/Huh7.5.1 cells increased both Gal‐9 production and NK cell cytotoxicity. Next, we investigated the source of Gal‐9 and the mechanism of Gal‐9 production. Deletion of CD14 + monocytes from PBMCs resulted in reduced Gal‐9 production in the coculture with JFH‐1/Huh7.5.1 cells. Gal‐9 production was driven by coculturing of PBMCs with apoptotic hepatocytes. Blocking integrin αv β3, a receptor for phosphatidylserine expressed on apoptotic cells, also resulted in decreased Gal‐9 production. Finally, we found that serum Gal‐9 levels were significantly higher in CHC patients than in healthy donors and patients who achieved sustained virologic response. Among CHC patients, serum Gal‐9 levels were significantly higher in patients with elevated alanine aminotransferase (ALT) than in those with normal ALT. Conclusion: These results demonstrate that CD14 + monocyte‐derived Gal‐9 increases NK cell cytotoxicity in HCV infection, which might be associated with liver injury and persistent infection. (Hepatology 2017;65:18‐31).